Adenocarcinoma arising from widespread heterotopic gastric mucosa in the cervicothoracic esophagus: a case report - Shohei Nogi; Kazuhiro Noma; Masashi Hashimoto; Takuya Kato; Naoaki Maeda; Shunsuke Tanabe; Yasuhiro Shirakawa; Toshiyoshi Fujiwara (Surgical Case Reports, 2023)
Abstract Background In Japan, about 6% of esophageal cancers are adenocarcinomas, although most of them arise from Barrett’s epithelium. Adenocarcinoma arising from heterotopic gastric mucosa (HGM) is very rare. Due to its rarity, there is no unified view on its treatment strategy and prognosis. Case presentation A 57-year-old man presented with a protruding lesion in the cervicothoracic esophagus that was detected by an upper gastrointestinal series at a medical checkup. Esophagoscopy revealed a 30 mm Type 1 tumor circumferentially surrounded by widespread HGM. Computed tomography (CT) and fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT showed no metastasis or invasion of the surrounding organs. We diagnosed the lesion as cT2N0M0 cStageIIB [Union for International Cancer Control (UICC) 8th Ed] cancer and performed subtotal esophagectomy with three-field lymph node dissection. The tumor was determined to be a well-differentiated adenocarcinoma arising from HGM, with deep invasion of the submucosa. The patient underwent no adjuvant therapy and has currently survived without any evidence of recurrence for 15 months. Conclusions Although the treatment for adenocarcinoma arising from HGM is basically the same as that for squamous cell carcinoma (SCC) of the esophagus, it is important to determine the treatment strategy based on the characteristics of the adenocarcinoma arising from HGM.